THE USE OF ARTIFICIAL INTELLIGENCE IN THE THERAPEUTIC MANAGEMENT OF PAPILLARY THYROID MICROCARCINOMA: A RANDOMIZED CONTROLLED TRIAL PROTOCOL - Ramona Elena Teiu; Tudor Florin Ursuleanu; Hlescu Cristian Stefan; Roxana Grigorovici; Andreea Roxana Luca; Maria Paula Comanescu; Alina Ionela Calin; Alexandru Grigorovici (Romanian Journal of Oral Rehabilitation)
Aim of the study The correct establishment of the therapeutic conduct in papillary thyroid cancer through the use of artificial intelligence (AI) models is essential in medical practice in diagnosing and establishing the prognosis of the disease, this aspect implies the most accurate and effective therapeutic approach. I aim to use AI models to obtain correct and favorable results for the diagnosis and prognosis of papillary thyroid cancer by conducting a clinical trial, in which we will use the diagnostic method optimized by artificial intelligence (AI) algorithms.The use of AI will avoid errors and increase performance in the interpretation of the doctor’s computed tomography (CT) scan and consequently, improve treatment planning.